East Canadian Light-bellied Brent Geese Branta bernicla hrota wintering at the Havre de Regnéville, France - Burgevin, Philippe (Wildfowl, 2013)
The Havre de Regnéville, France, is a major wintering site for the East Canadian HighÂ Arctic Light-bellied Brent Goose Branta bernicla hrota (LBBG) population, whichÂ winters mainly on well-known and well-studied sites along the Irish coast. ThisÂ wintering site has very little eelgrass Zostera sp. available and the geese regularly feedÂ on saltmarshes grazed by sheep. The Conservatoire du littoral is developing severalÂ studies to provide a better understanding of why LBBG use this site and to evaluateÂ the possible effects of climate change on its habitat. In particular, the proposed studyÂ will analyse a potential conflict of interests between biodiversity and agriculturalÂ activity in the area, to provide tools for a better coexistence between the geese andÂ sheep feeding on the saltmarshes.